(untitled) (Journal of Guidance and Counselling Studies, 2024)
The study was designed to investigate the influence of incentive administration on primary school teachers’ workforce retention. The need for the study came up as a result of high rate of teachers’ attrition in public schools in Abia State. The study adopted a descriptive survey with four research questions. The population of the study comprised all the primary school teachers in 63 primary school and a 30 item likert type questionnaire of incentive administration assessment scale (IAASQ) was administered in Umuahia North Local Government Area of Abia State. Data analysis of the research questions were done using mean and standard deviation while t-test was used to analyze the hypothesis at 0.05 level of significance. Based on the findings, it was recommended among other that there should be adequate incentives, frequency of incentives should be packaged, offered to the teachers, educational administrations should integrate teachers needs and aspirations, counsellors should have a bigger role to play in the lives of the teachers as they should be included in decision making in the school even for the policy-making. Conclusion was made.